Sex differences on quality of life and mental health outcomes when using a brief cognitive-behavioral skill building intervention with adolescent Syrian refugees: a secondary analysis - Kazandjian, Chant (2019)
Little is known about how sex as a biological variable may contribute to differences in quality of life (QOL) and mental health outcomes following a brief intervention among adolescent Syrian refugees. This paper explores the results of a secondary data analysis to investigate differences by sex on self-reported QOL and mental health outcomes among Syrian refugees who participated in a 7-session cognitive behavioral skills building intervention. A one group pretest–posttest design was used to deliver the intervention to 31 adolescent refugees (13–17 years; 15 male, and 16 female). At baseline, there were no significant differences between males and females on mean scores of depression, anxiety, or QOL. Post-intervention, self-reported scores for QOL and mental health were significantly different between sexes. Males demonstrated a significant decrease in anxiety scores compared to females. Among males only, significant decreases in depression and anxiety scores were observed with significant improvement in total QOL.